Analisis Pengaruh Current Ratio (Cr), Debt To Equity Ratio (DER), Return On Assets (ROA), Dan Price Earning Ratio (PER) Terhadap Harga Saham PT Nippon Indosari Corpindo Tbk Periode 2016 – 2022 (Per Kuartal) - Dandono, Yustinus Rawi; Kamila, Athaya (Management Research and Business Journal, 2024)
This study aims to determine the effect of the Liquidity Ratio variable projected with the Current Ratio (CR), the Solvency Ratio variable projected with the Debt To Equity Ratio (DER), the Profitability Ratio variable projected with Return On Assets (ROA) and the Growth Ratio variable projected with the Price Earning Ratio (PER) to stock prices. The method used in this study is multiple linear regression, involving the classical assumption test, followed by partial significance by using the T-test hypothesis test. The results showed that of the four independent variables analyzed, Current Ratio (CR) and Price Earning Ratio (PER) did not have a significant effect on stock prices. Meanwhile, the Debt To Equity Ratio (DER) and Return On Assets (ROA) variables have a significant influence on stock prices. The projection ability of the four independent variables on stock prices is 49.4% which is shown by the amount of adjusted R2, the remaining 50.6% is explained by other variables outside the research model such as ROE, NPM, PBV, EPS.